Reproductive cycle of the female Anisotremus scapularis (Tschudi, 1846) on the marine coast of Callao, basic knowledge to go towards its aquaculture - Carrera Santos, Lili J.; Fontes, Jéssica G.; Santos, Gustavo R. Cardoso Dos; Padilha, Mônica Costa; Opazo, Rafael (Frontiers in Marine Science, 2022)
Anisotremus scapularis is an important commercial species in Perú, being a prioritized species for the development of its aquaculture. The aim of the study was to establish the A. scapularis female reproductive cycle and reproductive strategy on the marine coast of Callao, through a seasonal sampling of wild specimens. The specimen collection was carried out between January 2019 to December 2020. Eighty-one female specimens were collected, and biometric indices were calculated such as condition factor (K) or gonadosomatic index (GSI), among others. The phases of the reproductive cycle were established by ovary histology in association with a steroid profile analysis performed by GC-EI-MS/MS. The reproductive strategy of A. scapularis was classified as asynchronous spawning with indeterminate fecundity. The average size at first maturity calculated as L100 was 25.3 cm. The GSI distribution was significantly higher in the specimens collected in summer than in the specimens collected in other seasons. The plasma concentration of 17β-estradiol, androstenedione-4, and testosterone per reproductive cycle phase was statistically significant. The distribution of 17β-estradiol plasma concentration in the specimens classified as spawning capable was higher than the specimens classified in other reproductive phases. The spawning capable phase was significantly and positively associated with the summer and autumn seasons. Thus, was possible to propose that the spawning season begins in late spring and until the middle of autumn in the Callao coast area. The recorded superficial temperature and daylight hours per day performed in the specimen’s collection area, allowed us to propose a thermo-photoperiod program for the management of broodstock. This should include the first cycle with temperatures between 12.5 - 13.5°C with an 11/13 light/darkness photoperiod, then the temperature should be increased to 16 - 17°C, with a 13/11 light/darkness photoperiod as a second cycle. Although the results of this study are limited to a specific area of the Callao coast, establishing the reproductive cycle and the spawning dynamics of A. scapularis females associated with environmental parameters, provides basic knowledge to improve the aquaculture of this species.